Formation of the System of Internal Factors of Investment Attractiveness of the Bank as an Object of M&A - Yaremenko, Nataliia (Видавництво Львівської політехніки, 2013)
In the article investment attractiveness of the Bank as a selection of objective-bank criterion in mergers or acquisitions is considered. The groups of internal environment factors of formation of investment attractiveness are defined and consequence of each of the groups is grounded. It is suggested to supplement internal factors indicators with the geographic coverage of the banking services market.
Keywords: investment; investment attractiveness of the bank; mergers and acquisitions (M&A); internal environment